Differential effects of white matter hyperintensities and regional amyloid deposition on regional cortical thickness - Tan, Chin Hong (2022)
White matter hyperintensities (WMH) and β-amyloid (Aβ) accumulation have both been linked to neurodegeneration in Alzheimer's disease (AD). However, the independent effects of global WMH and regional Aβ on the corresponding regional cortical thickness have not been investigated. Here, we evaluated 280 cognitively normal (CN), 450 mild cognitive impairment (MCI), and 63 individuals with AD dementia separately. In CN individuals, only WMH was associated with lower cortical thickness in fronto-temporal regions, independent of regional Aβ deposition in the corresponding cortical regions. In MCI individuals, the spatial pattern of independent WMH associations was predominantly in temporal and cingulate regions, while independent regional Aβ associations were now evident in temporal regions. No regional interactions were found. In non-demented individuals and MCI individuals alone, we found that global WMH, composite regional Aβ burden and cortical thickness in AD-associated regions all independently predicted progression to AD dementia. Our findings suggest that the independent effects of global WMH and regional Aβ on regional cortical thickness are spatially different, converging in temporal regions in MCI individuals.